Auden and MacNeice: Their Last Will and Testament – Thirties Classic or Existential Pause? - Sara R. GREAVES (E-REA)
This article focuses on the last chapter of W.H. Auden and Louis MacNeice’s 1937 travel narrative: Letters from Iceland, written entirely in terza rima and entitled “Their Last Will and Testament”. A humorous parody of a legal document, the 23-page-long poem consists of an inventory of miscellaneous bequests and their legatees, some of whom are prominent figures of the British establishment, considered against the sombre backdrop of the mounting threat of Nazism. The second part of the article deals more specifically with Auden, and the text is discussed in relation to Auden’s poetry as a whole as a rewriting of Dante’s Inferno, including his system of ‘contrapasso’ in the treatment of sinners, thereby shedding light on the poet’s quest for a language of (spiritual) healing. While the Iceland trip was an opportunity for Auden and MacNeice to remove themselves physically from the European theatre and observe it from outside, it also brought a near-the-bone reminder of what seemed to be already lost in terms of English poetry’s audience and role, and an experience of exile and alienation.